Trajectories of the infinitesimal mass around the triangular equilibrium points in elliptical restricted three bodies problem under oblate and radiating primaries for the binary systems - Singh, Nutan; Narayan, Ashutosh; Ishwar, B. (International Journal of Advanced Astronomy, 2015)
This paper describes the trajectory of the infinitesimal mass around L4 of the triangular equilibrium points for the binary systems in the elliptical restricted three body’s problem (ERTBP), where both oblate primaries are radiating. The solutions for the perturbed motion in the vicinity of L4 is given by u(f) and v(f) function .The stability of the infinitesimal mass around the triangular points is also studied by plotting u(f) and v(f) curve. It is found that radiation pressure, oblateness and eccentricity show a significant effect on the trajectory and stability of the infinitesimal mass around the triangular equilibrium points. Simulation technique has been used to design the trajectory of the binary systems (Achird, Luyten, α Cen AB, Kruger-60 and Xi-Bootis).